The influence of life cycle assessment and eco-innovation in ecodesign: A review - Arantes, Ariana [UNESP]; Hamamoto, Taís; Madeira, Ligia Maria Moura; Ometto, Aldo Roberto (My University, 2013)
This paper aims to make discussion about ecodesign, eco-innovation and the life cycle assessment (LCA) of products and/or processes in order contrast the topics to show their importance for sustainable management. For this, a classic literature review was conducted. The result showed that together they can strongly support the process of organizational decision making and improvement in product and process development or innovative processes. An exploratory study was then carried out in an OEM to see if the trends observed in the literature were confirmed. The conclusion of the study is that LCA acts indirectly as a support to the process of environmental innovation (eco-innovation), through ecodesign of products carried by product development and innovation teams, seeking opportunities for incremental or radical systemic improvements of existing products or development of new products.
Keywords: Eco-innovation; Ecodesign; Life cycle assessment; Product development process.